2015
DOI: 10.1007/s11695-015-1913-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Plication (LGP) as an Alternative to Laparoscopic Sleeve Gastrectomy (LSG) in Patients with Morbid Obesity: A Preliminary, Short-Term, Case-Control Study

Abstract: LGP for patients with severe obesity is safe and feasible with low rates of serious complications. As compared to LSG, LGP is associated to higher postoperative rate of nausea, lower operative cost, and lower EWL at 18-month follow-up (P = 0.041).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
2
19
0
2
Order By: Relevance
“…With the improvement of surgical techniques and endostapling devices, LSG had become a popular procedure for morbid obesity. According to previous studies [12][13][14][15][16][17][18][19][20][21], 53.8-80% of excess weight loss was obtained at 12 months postoperatively, and a similar result of 66.08% was noted in our study. However, the resection of the stomach with a long staple line was also accompanied by the innate risk of postoperative bleeding and leakage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With the improvement of surgical techniques and endostapling devices, LSG had become a popular procedure for morbid obesity. According to previous studies [12][13][14][15][16][17][18][19][20][21], 53.8-80% of excess weight loss was obtained at 12 months postoperatively, and a similar result of 66.08% was noted in our study. However, the resection of the stomach with a long staple line was also accompanied by the innate risk of postoperative bleeding and leakage.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the risk of bleeding or leakage might be reduced. As for weight reduction in LGCP, previous studies [12][13][14][15][16][17][18][19][20][21] showed that a 42.1-58.8% excess weight loss was obtained at 12 months after surgery. In our study, a comparable outcome of 48.02% was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well known that in Romania the average cost of LSG surgery is much higher than LGP. Data regarding the costs are unofficial and generally provided by private medical centers, but they correspond to already published results (26). Therefore, the financial variable favors LGP in this regard as a significantly cheaper intervention compared to other bariatric operations, including LSG.…”
Section: Discussionmentioning
confidence: 83%
“…The recent literature includes several studies that analyze short-and medium-term outcomes after LGP. However, the conclusions are contradictory and justify the maintenance of this surgery under investigation (11,14). Furthermore, there are few comparative studies of LGP and LSG procedures with a follow-up longer than three years (12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%